2020
DOI: 10.1002/cti2.1166
|View full text |Cite
|
Sign up to set email alerts
|

AAV9‐mediated AIRE gene delivery clears circulating antibodies and tissue T‐cell infiltration in a mouse model of autoimmune polyglandular syndrome type‐1

Abstract: Objectives Autoimmune polyglandular syndrome type‐1 (APS‐1) is a monogenic recessive disorder characterised by multiple endocrine abnormalities, chronic mucocutaneous candidiasis and high titres of serum autoantibodies. To date, no curative treatment is available; current therapies manage the symptoms rather than treating the cause and have major side effects. APS‐1 is caused by mutations in the autoimmune regulator (AIRE) gene. AIRE mediates central tolerance by directing the ectopic expression of tissue‐spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…In addition, current gene editing technologies do not allow for effective corrective gene therapy in the context of APECED syndrome. A recent study with Aire –/– mice demonstrated an adeno-associated virus (AAV) approach to correct AIRE deficiency, which was able to significantly reduce the development of autoimmune symptoms; however, this therapeutic effect was limited by technical issues linked to medullary thymic epithelial cells (mTECs) and AAV biology ( 49 ). First, the lack of mTEC-specific AAV serotype leads to the need of a direct injection inside the thymus and results only in a proportion of AIRE + mTECs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, current gene editing technologies do not allow for effective corrective gene therapy in the context of APECED syndrome. A recent study with Aire –/– mice demonstrated an adeno-associated virus (AAV) approach to correct AIRE deficiency, which was able to significantly reduce the development of autoimmune symptoms; however, this therapeutic effect was limited by technical issues linked to medullary thymic epithelial cells (mTECs) and AAV biology ( 49 ). First, the lack of mTEC-specific AAV serotype leads to the need of a direct injection inside the thymus and results only in a proportion of AIRE + mTECs.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that intrathymic injection of an AAV9-AIRE therapeutic restored AIRE expression in the thymus of Aire −/− mice. This AIRE gene delivery led to a significant increase in TSA expression and reduced serum autoantibodies in treated mice [ 40 ]. Thus, the level of Aire expression per mTECs and Aire+ mTECs frequency is both critical for maintaining self-tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…This is a crucial knowledge for the development of therapies. In fact, we have recently shown that direct injection of AIRE into the thymus of Aire-deficient mice was able to rescue the wild-type phenotype in 4-week-old mice but not in 12-week-old mice [ 40 ].…”
Section: Discussionmentioning
confidence: 99%